1960
DOI: 10.1103/physrev.120.1266
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Charge-Changing Collisions of Lithium Ionic and Atomic Beams

Abstract: Beams of Li + ions accelerated to kinetic energies in the range 10-475 kev were brought into charge equilibrium in the gases H 2 , He, and N2 and the fractional amounts of Li~, Li°, Li + , Li ++ , Li +++ measured. Because of the relatively large amount of Li~ in an equilibrated beam below 40 kev in energy in propane and nitrous oxide, limited investigations were carried out in these gases. The anomalously large Li ++ yield in helium at Li 7 energies below 100 kev was noted.By holding each separated charged con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1966
1966
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…For some of the ions which could be used in a-transfer reac tions, the cross sections for such collision processes are, however, very small, p articul arly for lithium. Charge exchange of positive and neutral lithium ions in different media exhibits cross sections ",1 % of those for the corresponding hydrogen charge exchange (25,26). In that case an extremely high primary beam intensity is required, which could not always be obtained with lithium beams.…”
Section: Ion Production Lithium Ion Sourcesmentioning
confidence: 98%
See 1 more Smart Citation
“…For some of the ions which could be used in a-transfer reac tions, the cross sections for such collision processes are, however, very small, p articul arly for lithium. Charge exchange of positive and neutral lithium ions in different media exhibits cross sections ",1 % of those for the corresponding hydrogen charge exchange (25,26). In that case an extremely high primary beam intensity is required, which could not always be obtained with lithium beams.…”
Section: Ion Production Lithium Ion Sourcesmentioning
confidence: 98%
“…Lithium beam currents exceed 1.5 jJ.A maximum and average 0.6 J.l.A. Charge exchange sources: The production of negative lithium ions by charge exchange has been shown to be less favorable if the charge exchange occurs between positive lithium ions and molecules of inert gases (25). The exchange of lithium ions in lithium vapor, however, may be much more favorable, but no cross sections have been measured.…”
Section: Ion Production Lithium Ion Sourcesmentioning
confidence: 99%
“…3 together with the earlier measurements of Allison et al [2], VanEck and Kistemaker [3], and Ogurtsov et al [4], and the theoretical calculations by Elizaga et al [5]. Previous experimental data coincide only to each other at the narrow energy range of 10 to 20 keV, and the connection of these data is found to be unsatisfactory in the other energy region.…”
Section: H 2 Moleculesmentioning
confidence: 85%
“…To the best of our knowledge, Allison et al [2], VanEck and Kistemaker [3], and Ogurtsov et al [4] reported the cross section measurements below 50 keV. Furthermore, few studies, e.g., Elizaga et al [5] tios were found to be almost unity in the entire investigated energy region from 0.18 to 1.5 keV/u.…”
Section: Introductionmentioning
confidence: 97%
“…This is approximately the difference between the ionization cross section calculated and measured (Puckett et al 1969) for He on Ar. In figure 4,1 show calculated stripping and ionization cross sections for Li ions on N. The stripping calculations are compared with calculation of Gillespie (1982), (crosses), for stripping of Li +0 ; the Li +0 measurements (3 the measured molecular cross sections) of Allison et al (1960), (open circles), Dmitriev et al (1962), (open triangles), and Horsdal Pedersen and Hvelplund (1973), (open squares); the Li +1 measurements of Allison et al (1960), (solid circles), Dmitriev et al (1962), (solid triangles), and Pivovar et al (1970), (solid squares); and the Li +2 measurements of Dmitriev et al (1962), (slashed triangle), and Pivovar et al (1970), (slashed squares). However, for He on Ar, the stripping and ionization cross sections are different, and in this case both sets of measurements on the stripping cross section are significantly lower than the calculation.…”
Section: Cross Section and Stopping Power Resultsmentioning
confidence: 99%